Evaluation of Leachate Recirculation Volume on Pollutant Removal and Biogas Production : a Case Study of Piyungan Landfill, Yogyakarta - Ika Wahyuning Widiarti; Rr Dina Asrifah; Mitha Puspitasari; Andini Shafa Saraswati; Assyfa Sopasari; Bima Marbun; Qorry Anissa Dewi (School of Postgraduate Studies, Diponegoro Univer, 2026)
Leachate recirculation is an on-site biological treatment method in which the generated leachate is returned to the waste mass. Its advantages include enhancing waste biodegradation, improving the removal efficiency of biochemical oxygen demand (BOD) and chemical oxygen demand (COD) in leachate, and promoting methane (CH₄) production. This study aimed to evaluate the effect of different leachate recirculation volumes on reducing pollutant concentrations in leachate from the Piyungan Landfill and enhancing biogas production from municipal solid waste. Leachate samples were collected from the Leachate Treatment Facility at the Piyungan Landfill, Bantul, Yogyakarta. Fresh waste samples representing the composition of municipal solid waste at the Piyungan Landfill were collected from the Purwoberhati 3R Waste Processing Facility (TPS 3R Purwoberhati), Kalasan. Three anaerobic bioreactors were operated: R0 (control), R1 (12 L/day), and R2 (24 L/day). Leachate recirculation over a 35-day period resulted in a decreasing trend in BOD and COD concentrations in R1 and R2. Pollutant concentrations in R0 could not be measured because no new leachate was generated. Based on the comparison between the initial and final concentrations, BOD removal efficiencies reached 98.4% in R1 and 92.0% in R2, while COD removal efficiencies reached 99.4% and 96.7%, respectively. Substantial reductions in heavy metal concentrations (Fe, Cr, and Cd) were also observed. During the recirculation process, methane (CH₄) was detected only in R2 on day 21 at a concentration of 0.23%, whereas carbon dioxide (CO₂) was detected throughout the experiment. The results demonstrate that leachate recirculation effectively reduced pollutant concentrations in leachate. However, the relatively short experimental duration limited the evaluation of methanogenesis; therefore, an increase in methane (CH₄) production could not be confirmed.